Exploring the internationalization strategy of higher education institutions and halal food ecosystem in Malaysia - H.,, Jamil; Wahab,, A. Y. A; Razak, A.R.A; Al -saari, Nurhidayu (Rynnye Lyan Resources, 2020)
Internationalization of higher education has become a strategic agenda of the development in Malaysia. In the age of globalization, the higher education sector experiences rapid growth with the increasing number of international students choosing Malaysia as a destination in pursuing their tertiary education. One of the crucial roles for Malaysian Higher Education Institutions (HEIs) is to successfully transform Malaysia to be the international hub for higher education. Globalization has changed the landscape of development in the higher education sector. Exploring the expectations, demands and preferences of international students is crucial in crafting the most suitable approach to enhance the internationalization strategy. As a multi-ethnic society with a majority Muslim population, Malaysian HEIs have the advantage to attract more international students through providing a ‘Muslim-friendly' Halal ecosystem. A dearth in HEIs internationalization literature discussing on Halal food ecosystem indicates the urgency to discover the potential of Halal ecosystem in accelerating the HEIs internationalization strategy. Hence, this paper seeks to explore the experiences of international students on Halal food ecosystem in Malaysia. A qualitative methodology using phenomenology approach was used to gather the research data from informants studied in public universities in Klang Valley area. The preliminary findings indicated that the Halal food ecosystem has a positive contribution to the HEIs internationalization strategy.